The Relationship Between Rail Transit and Industrial Agglomeration: Mediating Effect of Labor Agglomeration - Sun, Jing; Cherian, Jacob; Deng, Dasong; Yucel, Ali Gokhan; Sial, Muhammad Safdar; Fu, Qinghua; Cismas, Laura Mariana (Frontiers in Environmental Science, 2022)
The urban transit system is considered the backbone of any society as it heavily depends on economic progress. The railway transit system is crucial for any urban transit system. Based on this notion, the present research explores the industrial agglomeration in China's prefecture-level and cities from 2010 to 2020. The research analyses the processes of urban rail transit building, industrial agglomeration, and labor agglomeration due to the railway's transit network development. The findings are summarized in three main points; first, the agglomeration of the labor force is positively affected by the construction of urban rail transit infrastructure. Secondly, the development of railways infrastructure stimulates the agglomeration of manufacturing industries in and near urban population centers leading to the development of services industries. Third, the development and integration of railways networks with other transportation networks also optimize the allocation of capital in these areas as well. The development of railways network tends to bring economic and industrial development to these regions resulting in overall social development.